2020
DOI: 10.1101/2020.02.16.20023903
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical and immunologic features in severe and moderate forms of Coronavirus Disease 2019

Abstract: Background Since late December, 2019, an outbreak of pneumonia cases caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in Wuhan, and continued to spread throughout China and across the globe. To date, few data on immunologic features of Coronavirus Disease 2019 (COVID-19) have been reported. Methods In this single-centre retrospective study, a total of 21 patients with pneumonia who were laboratory-confirmed to be infected with SARS-CoV-2 in Wuhan Tongji hospital were included … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
498
7
19

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(564 citation statements)
references
References 20 publications
(25 reference statements)
40
498
7
19
Order By: Relevance
“…Consistent with previous study [20] , we also observed the decreased absolute number of CD3 + T cells in severe and mild patients (85.7%vs51.7%); moreover, the number of both CD4 + and CD8 + T cells were markedly lower in severe patients than mild patients. So far, the All rights reserved.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous study [20] , we also observed the decreased absolute number of CD3 + T cells in severe and mild patients (85.7%vs51.7%); moreover, the number of both CD4 + and CD8 + T cells were markedly lower in severe patients than mild patients. So far, the All rights reserved.…”
Section: Discussionsupporting
confidence: 92%
“…in the pathological process of COVID-19 . 10 We also found that the development of lymphopenia in severe patients was mainly related to the significantly decreased absolute counts of T cells, especially CD8 + T cells, but not to the absolute counts of B cells and NK cells. The decrease of T cells in the severe patient group reached its peak within the first week during the disease course, and then T cell numbers gradually increased during the second week and recovered to a comparable level to that of the mild patient group in the third week.…”
Section: Recent Studies Reported That the Sars-cov-2 Infection May Prmentioning
confidence: 52%
“…IL-6) in COVID-19 patients. 5,[8][9][10] However, it has remained largely unclear in the kinetics of lymphocyte subsets and inflammatory cytokines change in the peripheral blood during COVID-19. In this study, we longitudinally characterized the changes of lymphocyte subsets and cytokines profiles in the peripheral blood of COVID-19 patients with distinct disease severities.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that a subset of COVID-19 is characterized by the development of a cytokine storm syndrome (CSS) that resembles cytokine release syndrome (CRS) in chimeric antigen receptor (CAR)-T cell therapy (2,4,5). Hyperinflammation in COVID-19 is associated with elevation of pro-inflammatory cytokines including interleukin (IL)-6, IL-2R, IL-8, tumor necrosis factor-α, and granulocyte-colony stimulating factor (4,6), similar to the exuberant cytokine production by lunginfiltrating monocytes/macrophages and pneumocytes observed in SARS-CoV-1 and MERS-CoV infection (7). Alveolar inflammation and diffuse alveolar damage impair the infected lungs' local ability to participate in gas exchange, culminating in ARDS and necessitating mechanical ventilation (8).…”
Section: Resultsmentioning
confidence: 99%